Designing a Prototype for UPNM Academic and Student System Apply With Content Management Concept - Ramadhani, Ade Wahyu (2009)
The need of web application in the technology information era becomes very important. Nowadays, web application is a backbone of information system. Universiti Pertahanan Nasional Malaysia as one of public universities in Malaysia realizes that by applying web application technology in their institution to maximize from such application. UPNM Academic and Student System as the main academic system in the UPNM show improvement in managing their community by integrating web technology in their systems. This system use Web Content Management System (WCMS) in order to increase their performance and efficiency of work. It has two main entities, namely lecturer and student. Prototyping is needed as a model for designing this system which no fixed requirements. LPNM Academic and Student System is a system with complex rules, policies and requirements. Because of this complexity, prototype will play the role to assist the system to the stakeholder.